POLITICAL ENVIRONMENT SURROUNDING THE LAND CONFLICT IN AMURU DISTRICT ACHOLI SUB-REGION - Rusetuka, Muganzi Edson (Journal of Public Policy and Administration, 2019)
Purpose: To examine the political environment surrounding the land conflict in Amuru district Acholi sub-region. Methodology: The study employed a descriptive research design involving both qualitative and quantitative studies where 5 focus group discussions with 40 women and 40 men from Pabbo, Amuru and Lamogi sub counties of Amuru district and key interviews with 4 participants from Area Land Committee members and other leaders in the above sub counties. Findings: The findings indicate that over 90% of rural land is understood by the people who live there as under communal control/ownership. These communal land owners are variously understood as clans, sub-clans or extended families. Ethnic based land tensions fostered insecurity and instability in the Amuru as people could not walk around freely, access their gardens, were displaced and this in turn affected their ability to make a living through accessing the land. I also found that many women had relational access to land through their marriage and relationship with male kin and this seemed to give them fragile land rights. Men on the other hand had firm control over land and made final decisions relating to sales and land use. Unique contribution to theory, practice and policy: Having a study on land conflict in areas such as Amuru District in the Acholi-sub region which is one of the recently created districts in west Acholi in northern Uganda is very important. In addition land in Amuru district is a vital resource that defines the livelihoods, identity and relationship with ancestors of people. Research into political environment surrounding the land conflict in Amuru District Acholi sub-region will devise long term grassroots land dispute resolution structures into to increase the capacity of these structures by training, along with "˜sensitising' communities to their land rights, access, control and ownership rights. In the same way the study area and can be used to identify research gaps for further study.